The Local Food Crisis in Iraq Between Thoughts of the Malthusian Theory and the Agricultural Section Regression Reality - ناشور, الهام خزعل (Journal of Economics and Administrative Sciences, 2016)
Most countries in the world particularly developing countries, including Iraq,  facing  extremely dangerous problem with social and political dimensions, which is the emergence of the food crisis  problem ,the decrease in domestic food production in Iraq isn't meet the needs of its population food, due to the fact that the agricultural sector suffers from multiple natural ,economic  and human   problems .It is still below the level required to meet the needs of the population  of  food ,since food  at the forefront of priorities needed by the human . This represents indispensable  basic  necessity , so the responsibility of its availability permanently  in appropriate   quantity and  type should be done by the state and its related institutions  because it is a human right ,for this the presence of food crisis in Iraq and their increase is a big dilemma should be addressed through the availability of the necessary quantities  of food for the local population and improve the quality of food affordable that  they have. But we find that the state instead of  take strategic solutions  to face the crisis worked  to increase agricultural production tended to containment of crisis by imports from abroad,  this is what will put the state  in  large risks that are difficult to face in the future  ,and due to the importance of that issue, the study  reveal the reality of the food crisis in Iraq, and  the reasons leading to it, so that to find ways to address them.